Music Listening in Classical Concerts: Theory, Literature Review, and Research Program - Wald-Fuhrmann, Melanie; Egermann, Hauke; Czepiel, Anna; O’Neill, Katherine; Weining, Christian; Meier, Deborah; Tschacher, Wolfgang; Uhde, Folkert; Toelle, Jutta; Tröndle, Martin (Frontiers in Psychology, 2021)
Performing and listening to music occurs in specific situations, requiring specific media. Empirical research on music listening and appreciation, however, tends to overlook the effects these situations and media may have on the listening experience. This article uses the sociological concept of the frame to develop a theory of an aesthetic experience with music as the result of encountering sound/music in the context of a specific situation. By presenting a transdisciplinary sub-field of empirical (concert) studies, we unfold this theory for one such frame: the classical concert. After sketching out the underlying theoretical framework, a selective literature review is conducted to look for evidence on the general plausibility of the single elements of this emerging theory and to identify desiderata. We refer to common criticisms of the standard classical concert, and how new concert formats try to overcome alleged shortcomings and detrimental effects. Finally, an empirical research program is proposed, in which frames and frame components are experimentally manipulated and compared to establish their respective affordances and effects on the musical experience. Such a research program will provide empirical evidence to tackle a question that is still open to debate, i.e., whether the diversified world of modern-day music listening formats also holds a place for the classical concert – and if so, for what kind of classical concert.